Effect of a quadrivalent meningococcal ACWY glycoconjugate or a serogroup B meningococcal vaccine on meningococcal carriage: An observer-blind, phase 3 randomised clinical trial - Read, R; Baxter, D; Chadwick, DR; Faust, SN; Finn, A; Gordon, S; Heath, P; Lewis, D; Pollard, A; Turner, D; Bazaz, R; Ganguli, A; et al. (Lancet, 2014)
Background Meningococcal conjugate vaccines protect individuals directly, but can also confer herd protection by interrupting carriage transmission. We assessed the effects of meningococcal quadrivalent glycoconjugate (MenACWY-CRM) or serogroup B (4CMenB) vaccination on meningococcal carriage rates in 18-24-year-olds.